Doravirine dose Selection and 96-Week Safety and Efficacy versus Efavirenz in Antiretroviral Therapy-Naive Adults with HIV-1 Infection in a Phase IIb Trial. Issue 6 (August 2019) - Gatell, Jose M; Morales-Ramirez, Javier O; Hagins, Debbie P; Thompson, Melanie; Arastéh, Keikawus; Hoffmann, Christian; Raffi, François; Osiyemi, Olayemi; Dretler, Robin; Harvey, Charlotte; Xu, Xia; Plettenberg, Andreas; et al.
Background: The safety and efficacy of doravirine were compared with that of efavirenz as initial treatment of adults living with HIV-1 infection (NCT01632345). Methods: A Phase IIb double-blind trial with participants stratified by screening HIV-1 RNA (≤ or >100, 000 copies/ml) and randomized 1:1:1:1:1 to receive once-daily doravirine (25, 50, 100 or 200 mg) or efavirenz 600 mg (Part I) for up to 96 weeks, with open-label tenofovir disoproxil fumarate 300 mg/emtricitabine 200 mg (TDF/FTC). After dose selection at week 24, doravirine 100 mg was provided to participants receiving the other doses of doravirine and additional participants were randomized 1:1 to receive once-daily doravirine 100 mg or efavirenz 600 mg for 96 weeks with TDF/FTC (Part II). Primary outcomes were the proportion of participants with HIV-1 RNA <40 copies/ml at week 24, and central nervous system (CNS) adverse events (AEs) by weeks 8 and 24 (Parts I+II combined). Results: 210 and 132 participants were randomized in Parts I and II, respectively, and 216 (108 on doravirine 100 mg, 108 on efavirenz) were evaluable for Parts I+II combined. At week 24, the proportion of participants with HIV-1 RNA <40 copies/ml was 72.9% for doravirine 100 mg and 73.1% for efavirenz (difference −0.5 [95% CI −12.3, 11.2]). In addition, CNS AEs were reported by 26.9% and 47.2% of doravirine and efavirenz recipients, respectively (difference −20.4 [95% CI −32.6, −7.5]; P =0.002). Conclusions: Doravirine 100 mg with TDF/FTC demonstrated similar antiretroviral activity and superior CNS safety compared with efavirenz 600 mg with TDF/FTC.